Effects of commercial processing of selected non wood forest products on rural livelihood and resource sustainability in Oyo state (2013)
This study was conducted with a view to identify the socio-economic characteristics of processors of Vitellaria paradoxa and Parkia biglobosa; to examine the role of the rural dwellers in the sourcing and processing of V. paradoxa and P. biglobosa; to examine the different benefits that accrue to commercial processing of V. paradoxa and P. biglobosa and to investigate strategies put in place for sustainable use of V. paradoxa and P. biglobosa in the study area. Three (3) Local Government Areas were purposively selected for the study and purposive random sampling method was adopted for the selection of respondents. Primary data were obtained through the use of questionnaires while secondary data was gathered from relevant literature. Data collected were analyzed using descriptive statistical tools and gross margin analysis. The result showed that 90% of Vitellaria paradoxa and 94.3% of Parkia biglobosa processors were female. Majority of the processors of V. paradoxa (77.1%) and P. biglobosa (58%) fell within the age range of 21-40 years. Fruits of V. paradoxa (84.3%) and seeds of P. biglobosa (77.1%) were obtained from processors farmlands as a result of the relative availability of the trees on their farmlands. The remaining processors of V. paradoxa (15.7%) and P. biglobosa (22.9%) had no trees on their farmlands so they gathered the fruits and seeds from and around forest lands. 84.37% of V. paradoxa and 88.5% of P. biglobosa processors indicated that income was the main economic benefit derived from this business while social benefits highlighted by the respondents ranged from produce been used as food, medicine, condiment and cosmetic. The result also showed that processors of V. paradoxa incurred more costs, produced more output and had a higher average gross return in processing than P. biglobosa processors. The RORI for the processing business in the study area was 51% and 96%. To promote sustainability the people have adopted local means of sustaining production by preventing indiscriminate livestock grazing and bush burning.